Golgi fragmentation in amyotrophic lateral sclerosis, an overview of possible triggers and consequences - Sundaramoorthy, Vinod; Sultana, Jessica M.; Atkin, Julie D. (Frontiers in Neuroscience, 2015)
Amyotrophic Lateral Sclerosis (ALS) is an invariably fatal neurodegenerative disorder, which specifically targets motor neurons in the brain, brain stem and spinal cord. Whilst the etiology of ALS remains unknown, fragmentation of the Golgi apparatus is detected in ALS patient motor neurons and in animal/cellular disease models. The Golgi is a highly dynamic organelle that acts as a dispatching station for the vesicular transport of secretory/transmembrane proteins. It also mediates autophagy and maintains endoplasmic reticulum (ER) and axonal homeostasis. Both the trigger for Golgi fragmentation and the functional consequences of a fragmented Golgi apparatus in ALS remain unclear. However, recent evidence has highlighted defects in vesicular trafficking as a pathogenic mechanism in ALS. This review summarizes the evidence describing Golgi fragmentation in ALS, with possible links to other disease processes including cellular trafficking, ER stress, defective autophagy, and axonal degeneration.